Synthesis, Growth and characterization of Bis - glycine cobalt chloride dihydrate single crystal: A new semiorganic nonlinear optical material - Gobinathana, L.; Boopathy, K.b (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Single crystals of potential semiorganic nonlinear optical material of bis - glycine cobalt chloride dihydrate (BGCC) were grown by slow evaporation technique at room temperature. The structure of BGCC crystal was examined by single crystal X – ray diffraction analysis. The single crystal X – ray diffraction of BGCC reveals that the crystal belongs to monoclinic system with centrosymmetric space group. The powder X – ray diffraction analysis was carried out the reflection planes of the sample was confirmed and the peaks were indexed. Fourier transform infrared (FT – IR) spectroscopic analysis was used to confirm the presence of various functional groups in the grown crystal. UV – Vis – NIR spectral analysis of BGCC crystal shows that the crystal is transparent between the wavelengths 265 nm to 1100 nm. Vickers microhardness study revealed that the grown crystal belongs to soft material category. Dielectric constant and dielectric loss of BGCC crystal were measured in the frequency range of 100 Hz to 3 MHz. Thermal stability of the BGCC crystal was studied by thermogravimetric, differential thermal analysis and differential scanning calorimetric studies and found that the grown crystal is stable up to 220 °C.